PERANCANGAN APLIKASI RESEP MASAKAN TRADISIONAL INDONESIA MENGGUNAKAN PENDEKATAN AGILE PROCESS DENGAN MODEL EXTREME PROGRAMMING BERBASIS ANDROID - Sitompul, Elisawiah; Hutabri, Elbert (LPPM Universitas Putera Batam, 2023)
Almost all aspects of human life have now been touched by tehnological advances, one of which is food recipes. In the past, when you wanted to learn food recipes, you had to go through magazines and newspaper. Then was a change, food recipes can be found on the website in the form of the text and images. Then it developed in to video broadcast on youtube, which can access via a computer or smartphone. This development in the culinery field is indeed very helpful, but it still has weaknees namely, the information contained on the websites and videos is only for one type of food, if you want to find another dish you have to search again, this method also requires quite a lot of time to find food recipes according to your wants and needs, and the food recipes you are looking for are easily lost and easily forgotten because they cannot be stored permanently. So that with the application Android-based tradisional Indonesian food recipes, it can be accsessed mobile by using a smartphone.So this is quite helpful for users to make it easier to find information about the materials needed to how make to make them. The approach used is an agile process approach with an extreme programming model, then the design uses UML (Unified Modeling Language). Keywords: Food Recipes, Android, Agile Process, Extreme Programming